Analisis Yuridis Perlindungan Terhadap Kreditur Terkait Objek Jaminan Fidusia Berupa Benda Persediaan Di Kota Jambi - Raffles Raffles; Sinta Bela (Zaaken: Journal of Civil and Business Law, 2021)
Based on Article 21 of the Fiduciary Law, it is stated that the Fiduciary Giver can transfer inventory items that are the object of the Fiduciary Guarantee. However, to protect the interests of the Fiduciary Recipient, the transferred object must be replaced with an equivalent object. However, there is a fiduciary giver who transfers the inventory object that is the fiduciary object but does not replace the object as it should. So that two problem formulations are drawn, namely, first, how is legal protection against fiduciary guarantees with objects in the form of inventory items at grocery stores, second, how is legal protection for creditors related to fiduciary guarantee objects in the form of inventory objects. This study aims to determine and analyze the implementation of guarantees fiduciary with the object in the form of inventory and to find out and analyze the legal protection of creditors related to the object of fiduciary guarantee in the form of inventory; The type of research used is the type of empirical juridical research. The results of the study show that, legal protection for fiduciary guarantees with inventory objects includes: Fiduciary givers can transfer inventory objects that are objects of fiduciary guarantees in the usual ways and procedures in trading businesses, this provision does not apply if there has been a breach of contract by the debtor and or third party fiduciary. Second, the implementation of legal protection for creditors in a fiduciary guarantee agreement is born from the making of a notarial deed of imposition of fiduciary guarantees, and continues to be confirmed by registration with the Fiduciary Registration Office in order to obtain a guarantee certificate. Abstrak Berdasarkan Pasal 21 Undang-Undang Fidusia menegaskan bahwa Pemberi Fidusia dapat mengalihkan benda persediaan yang menjadi obyek Jaminan Fidusia. Namun demikian untuk menjaga kepentingan Penerima Fidusia, maka Benda yang dialihkan wajib diganti dengan obyek yang setara. Akan tetapi terdapat pemberi fidusia yang mengalihkan benda persediaa yang menjadi objek fidusia akan tetapi tidak mengganti objek tersebut sebagai mana mestinya. Sehingga di tarik dua rumusan masalah yaitu, pertama, Bagaimana Perlindungan Hukum terhadap jaminan fidusia dengan objek berupa benda persediaan pada toko kelontong, kedua, Bagaimana Pelaksanaan perlindungan hukum terhadap kreditur terkait objek jaminan fidusia berupa benda persediaan, Penelitian ini bertujuan untuk mengetahui dan menganalisis pelaksanaan jaminan fidusia dengan objek berupa benda persediaan dan untuk mengetahui dan menganalisis perlindungan hukum terhadap kreditur terkait objek jaminan fidusia berupa benda persediaan; Tipe penelitian yang digunakan adalah tipe penelitian yuridis empiris. Hasil penelitian menunjukan bahwa, Perlindungan Hukum terhadap jaminan fidusia dengan objek benda persediaan meliputi: “Pemberi fidusia dapat mengalihkan benda persediaan yang menjadi objek jaminan fidusia dengan cara dan prosedur yang lazim dilakukan di dalam usaha perdagangan, ketentuan ini tidak berlaku apabila telah terjadi cidera janji oleh debitur dan atau pemberi fidusia pihak ketiga. Kedua, Pelaksanaan perlindungan hukum bagi kreditur dalam suatu perjanjian jaminan fidusia lahir dari pembuatan Akta pembebanan jaminan fidusia yang dibuat secara notariil, dan terus dipertegas dengan pendaftaran ke Kantor Pendaftaran Fidusia demi mendapatkan sertifikat jaminan.